A four digit integer a b c d satisfies the equation ( a b c d ) 2 = w x y z a b c d where a , b , c , d , w , x , y , z are not necessarily distinct digits and a = 0 , w = 0 . What is the value of w x y z ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
@Daniel Liu, sorry for this, but I just checked one of my programs for 4-digit automorphic numbers and found that 9376^2 = 89709376, and so I got the answer. :D
@
w
i
l
l
b
e
u
s
e
d
t
o
m
e
a
n
"
n
o
t
i
n
t
e
r
e
s
t
e
d
i
n
t
h
i
s
d
i
g
i
t
a
t
p
r
e
s
e
n
t
.
"
S
i
n
c
e
d
2
=
@
d
.
d
=
5
o
r
6
.
N
o
t
e
1
0
n
(
1
4
x
+
x
y
)
=
1
0
n
+
1
x
+
1
0
n
(
4
x
+
x
y
)
.
S
i
m
i
l
a
r
s
e
p
a
r
a
t
i
o
n
i
s
d
o
n
e
b
e
l
o
w
.
A
l
s
o
n
o
t
e
t
h
a
t
s
q
u
a
r
e
s
h
o
u
l
d
h
a
v
e
8
t
e
r
m
s
.
⟹
a
>
1
0
8
=
3
1
6
2
.
W
e
h
a
v
e
(
1
0
3
a
+
1
0
2
b
+
1
0
1
c
+
d
)
2
=
1
0
6
∗
(
a
2
)
+
1
0
5
∗
(
2
a
b
)
+
1
0
4
∗
(
b
2
+
2
∗
a
c
)
+
1
0
3
∗
(
2
a
d
+
2
b
c
)
+
1
0
2
∗
(
c
2
+
2
b
d
)
+
1
0
∗
(
2
c
d
)
+
d
2
.
S
o
f
o
r
d
=
5
,
a
b
c
d
2
=
1
0
6
∗
(
a
2
)
+
1
0
5
∗
(
2
a
b
)
+
1
0
4
∗
(
b
2
+
2
∗
a
c
)
+
1
0
3
∗
(
1
0
a
+
2
b
c
)
+
1
0
2
∗
(
c
2
+
1
0
b
)
+
1
0
∗
(
1
0
c
)
+
5
2
.
=
1
0
6
∗
(
a
2
)
+
1
0
5
∗
(
2
a
b
)
+
1
0
4
∗
(
b
2
+
2
∗
a
c
+
a
)
+
1
0
3
∗
(
2
b
c
+
b
)
+
1
0
2
∗
(
c
2
+
c
)
+
2
5
.
S
o
f
o
r
d
=
6
,
a
b
c
d
2
=
1
0
6
∗
(
a
2
)
+
1
0
5
∗
(
2
a
b
)
+
1
0
4
∗
(
b
2
+
2
∗
a
c
)
+
1
0
3
∗
(
1
2
a
+
2
b
c
)
+
1
0
2
∗
(
c
2
+
1
2
b
)
+
1
0
∗
(
1
2
c
)
+
6
2
.
=
1
0
6
∗
(
a
2
)
+
1
0
5
∗
(
2
a
b
)
+
1
0
4
∗
(
b
2
+
2
a
c
+
a
)
+
1
0
3
∗
(
2
a
+
2
b
c
+
b
)
+
1
0
2
∗
(
c
2
+
2
b
+
c
)
+
1
0
∗
(
2
c
)
+
3
6
.
d
=
6
:
−
W
e
s
h
a
l
l
i
n
v
e
s
t
i
g
a
t
e
e
a
c
h
d
i
g
i
t
a
t
a
t
i
m
e
i
n
t
h
e
s
q
u
a
r
e
e
x
p
r
e
s
s
i
o
n
w
i
t
h
t
h
e
h
e
l
p
o
f
a
b
o
v
e
.
(
1
0
1
)
t
h
d
i
g
i
t
=
c
1
0
∗
(
2
c
)
+
3
6
L
e
t
u
s
a
s
s
u
m
e
c
f
r
o
m
0
t
o
9
.
S
t
o
p
w
h
e
r
e
a
s
s
u
m
e
d
v
a
l
u
e
i
s
w
h
a
t
w
e
g
e
t
b
y
c
a
l
c
u
l
a
t
i
o
n
.
L
e
t
c
=
1
−
−
−
−
−
−
−
−
1
0
∗
2
+
3
6
=
5
6
,
c
=
5
.
.
X
X
X
.
.
.
.
.
.
.
.
.
.
c
=
2
,
−
−
−
−
−
−
−
1
0
∗
4
+
3
6
=
7
6
.
.
c
=
7
.
.
X
X
X
T
h
e
p
a
t
t
e
r
n
i
s
+
1
t
o
a
s
s
u
m
e
d
v
a
l
u
e
w
h
i
l
e
+
2
t
o
c
a
l
c
u
l
a
t
e
d
v
a
l
u
e
.
S
i
n
c
e
w
e
h
a
v
e
1
0
∗
2
a
.
S
o
c
=
3
−
−
−
−
c
a
l
c
u
l
a
t
e
d
c
=
9
.
.
X
X
X
.
.
.
.
.
.
c
=
4
−
−
−
−
c
a
l
c
u
l
a
t
e
d
c
=
1
1
=
@
1
.
.
X
X
X
.
.
.
.
.
.
.
.
.
.
c
=
5
−
−
−
−
−
−
c
=
3
.
.
X
X
X
c
=
6
−
−
−
−
−
−
−
−
−
C
=
5
.
.
X
X
X
X
.
.
.
.
.
.
c
=
7
−
−
−
−
−
−
−
−
−
−
c
=
7
.
.
.
.
C
h
e
c
k
7
6
2
=
5
7
7
6
O
K
.
c
=
7
.
(
1
0
2
)
t
h
d
i
g
i
t
=
b
1
0
2
∗
(
c
2
+
2
b
+
c
)
+
1
0
∗
(
2
c
)
+
3
6
=
1
0
2
(
5
6
+
2
b
)
+
1
0
∗
(
1
4
)
+
3
6
=
5
6
0
0
+
1
0
2
(
2
b
)
+
1
4
0
+
3
6
=
5
7
7
6
+
1
0
2
∗
(
2
b
)
.
L
e
t
b
=
1
−
−
−
−
−
−
−
−
5
7
7
6
+
1
0
2
∗
2
=
5
7
7
6
+
2
0
0
=
5
9
7
7
6
,
b
=
9
.
.
X
X
X
.
.
.
.
.
.
.
b
=
2
,
−
−
−
−
−
7
7
6
+
4
0
0
=
1
1
7
6
.
.
b
=
1
.
.
X
X
X
S
a
m
e
p
a
t
t
e
r
n
a
s
a
b
o
v
e
.
.
b
=
2
+
1
=
3
−
−
−
−
b
=
1
+
2
=
3
.
.
C
h
e
c
k
.
3
7
6
2
=
1
4
1
3
7
6
G
O
O
D
.
b
=
3
.
(
1
0
3
)
t
h
d
i
g
i
t
=
a
n
e
g
l
e
c
t
p
o
w
e
r
h
i
g
h
e
r
t
h
a
n
3
.
1
0
3
∗
(
2
a
+
2
b
c
+
b
)
+
1
0
2
∗
(
c
2
+
2
b
+
c
)
+
1
0
∗
(
2
c
)
+
3
6
=
1
0
3
(
2
a
+
4
5
)
+
1
0
2
(
8
5
)
+
1
4
0
+
3
6
=
1
0
3
∗
(
2
a
)
+
1
0
3
∗
4
5
+
1
0
2
∗
8
5
+
1
7
6
.
=
1
0
3
∗
(
2
a
)
+
4
5
0
0
0
+
6
2
0
0
+
1
7
6
=
1
0
3
∗
(
2
a
)
+
5
1
3
7
6
.
B
u
t
a
@
@
@
>
3
1
6
2
,
a
n
d
w
e
h
a
v
e
a
l
r
e
a
d
y
3
7
6
.
S
o
w
e
s
t
a
r
t
w
i
t
h
a
=
3
.
a
=
3
−
−
−
−
−
−
6
0
0
0
+
−
5
1
3
7
6
=
5
7
3
7
6
.
.
⟹
a
=
7
.
.
X
X
X
.
.
.
.
.
.
.
.
.
.
A
g
a
i
n
s
a
m
e
p
a
t
t
e
r
n
a
s
a
b
o
v
e
.
A
s
s
u
m
e
+
1
−
−
−
−
c
a
l
c
u
l
a
t
e
d
+
2
.
a
=
4
−
−
−
−
−
−
−
c
a
l
c
u
l
a
t
e
d
.
.
a
=
9
.
.
X
X
X
.
.
.
.
.
.
a
=
5
−
−
−
−
−
−
c
a
l
c
u
l
a
t
e
d
.
.
a
=
1
1
=
@
1
.
.
.
.
.
.
a
=
6
−
−
−
−
c
a
l
c
u
l
a
t
e
d
.
.
a
=
3
.
.
X
X
X
.
a
=
7
−
−
−
−
−
−
−
c
a
l
c
u
l
a
t
e
d
.
.
a
=
5
.
.
X
X
X
.
.
.
.
.
.
.
a
=
8
−
−
−
−
−
c
a
l
c
u
l
a
t
e
d
.
.
a
=
7
.
.
X
X
X
.
.
.
.
a
=
9
−
−
−
−
c
a
l
c
u
l
a
t
e
d
.
.
a
=
9
.
C
h
e
c
k
i
n
g
9
3
7
6
2
=
8
7
9
0
9
3
7
6
,
O
K
.
S
o
w
x
y
z
=
8
7
9
0
.
Proof of d=5 does not work, I will give shortly. In fact I had typed it but by mistake delete it!!
Problem Loading...
Note Loading...
Set Loading...
We see that a b c d × a b c d = w x y z a b c d .
Subtracting a b c d from both sides, we get a b c d ( a b c d − 1 ) = w x y z 0 0 0 0 . Thus,
1 0 0 0 0 ∣ a b c d ( a b c d − 1 )
In addition, since a b c d and ( a b c d − 1 ) are consecutive integers, one must be even, and the other must be odd. Hence, either
[ 6 2 5 ∣ a b c d 1 6 ∣ ( a b c d − 1 ) or
[ 1 6 ∣ a b c d 6 2 5 ∣ ( a b c d − 1 )
We can substitute x = a b c d to make notation easier.
Case 1
In this case, 6 2 5 ∣ x and 1 6 ∣ x − 1 . We let x = 6 2 5 k . Thus 1 6 ∣ 6 2 5 k − 1 , or 6 2 5 k − 1 ≡ 0 ( m o d 1 6 ) .
This is simplified to k − 1 ≡ ( m o d 1 6 ) , where k = 1 is the obvious answer.
However, when we plug back in k = 1 to solve for x , we find that x = 6 2 5 , which is only a three-digit number. Thus, this case yields no solutions.
Case 2
In this second case, 1 6 ∣ x , so 6 2 5 ∣ x − 1 . We let x − 1 = 6 2 5 k . Thus, 1 6 ∣ 6 2 5 k + 1 , or 6 2 5 k + 1 ≡ 0 ( m o d 1 6 )
This can be simplified to k + 1 ≡ ( m o d 1 6 ) , at which k = 1 5 is an obvious solution.
Thus, x − 1 = 6 2 5 ∗ 1 5 = 9 3 7 5 , or x = a b c d = 9 3 7 6 .
Finally, ( 9 3 7 6 ) 2 = 8 7 9 0 9 3 7 6 (we confirm the last 4 digits of the result is the same as the squared number) and we get an answer of 8 7 9 0 .